2001
DOI: 10.1103/physrevb.64.220506
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Hall effect in superconductingMgB2films

Abstract: We have investigated the temperature and magnetic field dependence of the Hall coefficient of two wellcharacterized superconducting MgB 2 films (T c0 ϭ38.0 K) in both the normal and superconducting states. Our results show that the normal-state Hall coefficient R H is positive and increases with decreasing temperature, independent of the applied magnetic field ͑to 8 T͒. We find that R H Ϫ1 ϰT(40-300 K) and cot H ϰT 2 (100-300 K). As the sample is cooled below T c (H), R H decreases rapidly with temperature and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
33
6

Year Published

2002
2002
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 27 publications
9
33
6
Order By: Relevance
“…In our earlier work on polycrystalline samples [2], we confirmed that the majority charge carriers were holelike, which was consistent with theoretical estimates [10]; subsequently, similar results were also reported for polycrystalline MgB 2 thin films [11]. To the best of our knowledge, the in-plane Hall effect for MgB 2 has not been previously studied; thus, measurement of the ab-plane Hall effect for c-axis-oriented MgB 2 thin films should provide significant input for future investigations of its electronic transport properties and vortex dynamics.…”
Section: Introductionsupporting
confidence: 77%
See 3 more Smart Citations
“…In our earlier work on polycrystalline samples [2], we confirmed that the majority charge carriers were holelike, which was consistent with theoretical estimates [10]; subsequently, similar results were also reported for polycrystalline MgB 2 thin films [11]. To the best of our knowledge, the in-plane Hall effect for MgB 2 has not been previously studied; thus, measurement of the ab-plane Hall effect for c-axis-oriented MgB 2 thin films should provide significant input for future investigations of its electronic transport properties and vortex dynamics.…”
Section: Introductionsupporting
confidence: 77%
“…As the T was increased from the T c , the R H decreased linearly up to 130 K (T * ) and then deviated from that linear behavior at higher T , suggesting that the electronic transport mechanism changes at around 130 K. The T * was observed to be independent of magnetic fields up to 5 T. This feature is somewhat different from previous results for polycrystalline bulk [2] and thin-film samples [11] for which the R H exhibited the same T dependence over the entire T range from the T c to 300 K. These results suggest that MgB 2 might have different transport mechanisms in the in-plane and the out-of-plane directions. A similar distinct T -dependence around 150 K was also observed in the thermoelectric power measurements [3,4]; the thermoelectric power increased linearly with increasing T up to around 150 and then showed a downward deviation from linearity.…”
Section: Resultscontrasting
confidence: 55%
See 2 more Smart Citations
“…fig 5. R H is positive at the normal state (like many HTSs) indicating that conduction is done by hole-like and not electron-like carriers. Below T c in the mixed state, some sign reversal (single or double) of R H appears at temperatures between 40 and 100 K. The sign change was detected in many different HTSs [21,22] and even in the newly discovered MgB 2 superconductor [23]. The field dependencies of mobility at different temperatures from 110 to 250 K are shown in fig 6.…”
Section: Methodsmentioning
confidence: 94%